Materials engineering and automatic control III : selected, peer reviewed papers from the 3 rd International Conference on Materials Engineering and Automatic Control (ICMEAC 2014), May 17-18, 2014, Tianjin, China - Wang, Shoujun (Applied mechanics and materials, 2014)
Collection of selected, peer reviewed papers from the 3 rd International Conference on Materials Engineering and Automatic Control (ICMEAC 2014), May 17-18, 2014, Tianjin, China. The 182 papers are grouped as follows: Chapter 1: Advanced Materials Engineering and Materials Processing Technologies, Chapter 2: Mechanical Engineering and Dynamics, Liquids and Gases Mechanics, Applied Mechanics in Technological Processes, Structural Design, Chapter 3: Instrumentation, Measurement and Testing Technologies, Analysis and Calculations Methodology, Chapter 4: Technologies of Power Systems, Energy and T.